Retrospective analysis of disease profile and percentage of COVID positivity among patients presenting to paediatric triage of a tertiary care hospital during COVID pandemic lockdown period - Pathak, Gargi H.; Chauhan, Anuya; Beniwal, Sunita (International Journal of Contemporary Pediatrics, 2021)
Background: Currently, limited reports analyze pediatric patients infected with SARS-Covid-19. We conducted this study with the purpose of assessing the disease profile and percentage of COVID positivity among pediatric patients presenting to our triage area. Methods: A retrospective quantitative observational study was conducted in the pediatric triage area, department of pediatrics, Civil hospital campus, Ahmedabad, India. Patients aged 0-12 years were included with the study period from 1stApril to 30th June, 2020. Patients fulfilling the ICMR testing criteria were considered as suspected COVID patients and tested for COVID. Remaining patients were triaged and managed either on OPD basis or admitted in PICU, NICU or pediatric ward. Also, data of OPD attendance rate and immunization rates of 3 months (April, May and June) of 2019 and 2020 were collected from pediatric OPD and vaccination center. Results: A total of 709 patients presented in the triage out of which 35.5% were neonates, 28.6% were between 1-12 month, 23.2%were between 1-5 years and 12.6% were between 5-12 years. 12 out of 97 suspected patients tested positive for COVID 19. Among COVID positive patients, 50% had uncomplicated illness or mild pneumonia, while 50 % had critical illness and were admitted in COVID ICU. Mortality among non COVID patients was 22.7%, and among COVID patients was 16.6%. A sharp fall was noted in the OPD attendance (10 times) and immunization rates (3 times) this year compared to last year. Conclusions: Incidence of COVID positivity was comparable to the studies done in other countries. Even during the pandemic peak, the major chunk of pediatric admissions still belonged to the non COVID conditions. The drastic fall in immunization rates can have implications in the form of re-emergence of vaccine preventable diseases in the coming times.